TINJAUAN YURIDIS TENTANG BENTUK-BENTUK PERLINDUNGAN HUKUM BAGI TENAGA KERJA YANG BEKERJA DI LAUT - Marsidah, Marsidah (Solusi, 2018)
The risk of danger at sea is very large, shipping companies must guarantee the protection of workers on ships related to the risk of marine hazards without exception. The issue published in this discussion is a discussion of the legal form for workers who work at sea based on Law No. 13 of 2003 and number 7 in 2000. The type of research used in this research is normative juridical by assessing fuel-Section Number 13 of 2003 concerning employment and Government Regulation Number 7 of 2000 concerning seafarers and the responsibility of seafarers. Regarding the legal form for workers who work with legal protection for work time, occupational safety and health, and wages. In addition, in accordance with the applicable law in the Jamsostek Permit the right to wages, housing and house rights, the right to leave, the right to the time of illness or accident.